Multiparametric Renal Magnetic Resonance Imaging: Validation, Interventions, and Alterations in Chronic Kidney Disease - Cox, Eleanor F.; Buchanan, Charlotte E.; Bradley, Christopher R.; Prestwich, Benjamin; Mahmoud, Huda; Taal, Maarten; Selby, Nicholas M.; Francis, Susan T. (Frontiers in Physiology, 2017)
Background: This paper outlines a multiparametric renal MRI acquisition and analysis protocol to allow non-invasive assessment of haemodynamics (renal artery blood flow and perfusion), oxygenation (BOLD T2*) and microstructure (diffusion, T1 mapping). Methods: We use our multiparametric renal MRI protocol to provide 1) a comprehensive set of MRI parameters (renal artery and vein blood flow, perfusion, T1, T2*, diffusion (ADC, D, D*, fp) and total kidney volume) in a large cohort of healthy participants (127 participants with mean age of 41 ± 19 years) and show the MR field strength (1.5 T versus 3 T) dependence of T1 and T2* relaxation times; 2) the repeatability of multiparametric MRI measures in eleven healthy participants; 3) changes in MRI measures in response to hypercapnic and hyperoxic modulations in six healthy participants; and 4) pilot data showing the application of the multiparametric protocol in eleven patients with Chronic Kidney Disease (CKD). Results: Baseline measures were in-line with literature values, and as expected, T1 values were longer at 3 T compared with 1.5 T, with increased T1 corticomedullary differentiation at 3 T. Conversely, T2* was longer at 1.5 T. Inter-scan coefficients of variation (CoVs) of T1 mapping and ADC were very good at <2.9 %. Intra class correlations (ICCs) were high for cortex perfusion (0.801), cortex and medulla T1 (0.848 and 0.997 using SE-EPI), and renal artery flow (0.844). In response to hypercapnia, a decrease in cortex T2* was observed, whilst no significant effect of hyperoxia on T2* was found. In CKD patients, renal artery and vein blood flow, and renal perfusion was lower than for healthy participants. Renal cortex and medulla T1 was significantly higher in CKD patients compared to healthy participants, with corticomedullary T1 differentiation reduced in CKD patients compared to healthy participants. No significant difference was found in renal T2*. Conclusions: Multiparametric MRI is a powerful technique for the assessment of changes in structure, haemodynamics and oxygenation in a single scan session. This protocol provides the potential to assess the pathophysiological mechanisms in various aetiologies of renal disease, and to assess the efficacy of drug treatments.